1986
DOI: 10.1002/j.1460-2075.1986.tb04375.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA gyrase complex with DNA: determinants for site-specific DNA breakage.

Abstract: DNA gyrase catalyses DNA supercoiling by making a transient double‐stranded DNA break within its 120‐150 bp binding site on DNA. Addition of the inhibitor oxolinic acid to the reaction followed by detergent traps a covalent enzyme‐DNA intermediate inducing sequence‐specific DNA cleavage and revealing potential sites of gyrase action on DNA. We have used site‐directed mutagenesis to examine the interaction of Escherichia coli gyrase with its major cleavage site in plasmid pBR322. Point mutations have been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
3
40
0
1
Order By: Relevance
“…Propagation of the plasmids was in E. coli DH5ao [F-endA1 hsdR17 (rK-MK+) supE44 thi-J DNA sequencing. DNA sequences were determined both by the chain termination method (27) and by the chemical modification method (19) as previously described (6,30).…”
Section: Methodsmentioning
confidence: 99%
“…Propagation of the plasmids was in E. coli DH5ao [F-endA1 hsdR17 (rK-MK+) supE44 thi-J DNA sequencing. DNA sequences were determined both by the chain termination method (27) and by the chemical modification method (19) as previously described (6,30).…”
Section: Methodsmentioning
confidence: 99%
“…The 5'-end-labeling, using T4 polynucleotide kinase, was carried out as described previously (6 (29). Cells were grown in 10 liters of L broth to an optical density at 600 nm of -1.5, pelleted, washed with 50 mM Tris hydrochloride, pH 8.0-10% glycerol-1 mM dithiothreitol, and stored at -70°C as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…Addition of detergent to gyrase-DNA complexes formed in the presence of oxolinic acid results in site-specific double-stranded DNA breakage and covalent attachment of the gyrase A subunits to each 5'-phosphate end via tyrosine (Tyr)-122 (6,7,9,15,22,31). Thus, the A subunits appear to promote DNA breakage and reunion during catalysis, a process interrupted by quinolone inhibitors.…”
mentioning
confidence: 99%
“…In pBR322, analysis of oxo/gyrase-induced DNA cleavage sites in vivo has suggested a weak consensus sequence; 5Ј RNNNRNR(TG)GRYC(TG)YNYN(GT)NY 3Ј, with cleavage occurring 5Ј of the sequence GRYC (underlined) on both strands (Lockshon and Morris, 1985). A mutational analysis of the major site in pBR322 revealed that cleavage is sensitive to point mutations at the cleavage site (residues G and C in the sequence GRYC) (Fisher et al, 1986). However, it should be recalled that this consensus might not be exclusive as DNA gyrase binds efficiently and breaks DNA in the pSC101 par locus and in the central region of bacteriophage Mu at sites that differ from it (Wahle and Kornberg, 1988;Pato et al, 1990).…”
Section: Introductionmentioning
confidence: 99%